Genomic and Genetic Disorders Biobank. (20th March 2015) - Fusco, Carmela; Micale, Lucia; Pellico, Maria Teresa; D'Addetta, Ester Valentina; Augello, Bartolomeo; Mandriani, Barbara; De Nittis, Pasquelena; Cocciadiferro, Dario; Malerba, Natascia; Sacco, Michele; Zelante, Leopoldo; Merla, Giuseppe
The Genomic and Genetic Disorders Biobank (GGDB, formerly Genomic Disorders Biobank) was established in 2006 as an internal bioresource to the Medical Genetics Unit at Casa Sollievo della Sofferenza Hospital (Italy) to collect and store biospecimens from affected individuals with genomic-disorders (e.g. microdeletion and duplication syndromes). Since 2009 the Bioresource has joined the Telethon Network of Genetic Biobanks and has expanded the collection to also include Mendelian genetic diseases. The GGDB now gathers wholly annotated clinical and longitudinal data and biological samples from affected and healthy donors, according to standard ethical principles. Biospecimens are available to the international scientific community for research projects in the field of the pathologies collected and stored in the GGDB.